Evaluating a toolkit to assist rural communities in developing end of life care [research project] / by Hilary Mettam. - Mettam, Hilary (My University, 2009)
Study location : Emo, Northwestern Ontario.

The need for community-based, client-centred end-of-life care is particularly evident in rural areas in order to allow people to die amongst their family and friends. However, resources are limited and there is often a lack of coordination and communication between the agencies responsible for providing rural community care. In 2008 the North West Community Care Access Centre (CCAC) received funding from the Local Health Integration Network (LHIN) to create a resource, specifically a “toolkit”, that would guide communities in the development of local palliative and end-of- life care programs and facilitate seamless, integrated care. The outcome of this funding was a document called “Building A Community End of Life Care Program: A Toolkit for Action”, which is referred to here as the Toolkit (see Appendix A). With the Toolkit now being disseminated throughout the region, this project aims to describe how it is being used by certain communities in Northwestern Ontario and how it might be improved to optimize its value for program planning and development. This evaluation is being supported by the Interdisciplinary Capacity Enhancement (ICE) program of research titled “Timely Access and Seamless Transitions in Rural Palliative/End-of-Life Care”. This five year program of research is being funded by the Canadian Institutes of Health Research (CIHR) and involves a team of researchers from across Canada working on ten different projects. Specifically, this evaluation is being supported by ICE Project 9, “Refinement and testing of a conceptual model for developing and delivering rural palliative care programs”, which is being led by Dr. Mary Lou Kelley of Lakehead University and Dr. Allison Williams of McMaster University.
Keywords: Terminal care; Palliative treatment; Palliative Care